Plant Growth-Promoting Microbes for Resilient Farming Systems: Mitigating Environmental Stressors and Boosting Crops Productivity—A Review - Assiya Ansabayeva; Murat Makhambetov; Nazih Y. Rebouh; Mostafa Abdelkader; Hani S. Saudy; Karim M. Hassan; Mohamed A. Nasser; Mahmoud A. A. Ali; Mohamed Ebrahim (Horticulturae)
This review delves into the role of plant growth-promoting microbes (PGPMs) in sustainable agriculture by enhancing soil health, improving plant stress tolerance, and controlling diseases. PGPMs, which include bacteria, fungi, and other microorganisms, are increasingly recognized as important contributors to promoting eco-friendly agricultural practices. Their ability to improve nutrient availability, stimulate plant growth, and protect crops from environmental stressors makes them a cornerstone for resilient and efficient farming systems. By reducing dependency on synthetic fertilizers and pesticides, PGPMs play a vital role in preserving environmental resources, minimizing greenhouse gas (GHG) emissions, and combating climate change’s negative impacts. This article thoroughly explores the complex interactions between PGPMs, soil nutrients, plant pathogens, and abiotic stressors. It also examines how these interactions influence phytohormone production and signaling pathways, ultimately impacting crop growth and development. Furthermore, this review discusses how PGPMs enhance nutrient uptake, modulate plant immune responses, and improve stress resilience, offering a holistic understanding of their multifaceted contributions to farming. By synthesizing current research and highlighting future directions, this review underscores the potential of PGPMs to revolutionize agricultural activities, ensuring food security and environmental sustainability in the face of global challenges.